Entrepreneurship Education at Universities: Suggestion for a Model Using Financial Support. (3rd July 2015) - Başçı, Eşref Savaş; Alkan, Reha Metin
Abstract: The public sector is not the only one that creates more and better jobs in developed countries. In addition, the private sector seems to have a major role in solving the problem of unemployment. But according to recent studies, the oldest and largest private companies cannot seem to provide new opportunities to combat unemployment. This poses a question: which type of companies can provide employment to those individuals seeking it? Lately, it seems that only companies which use advanced technology and startup companies can provide new jobs to those seeking employment. Currently, the mission of the university as an institution has changed. Education of entrepreneurship is the one of the important areas of study in universities all around the world. Developments on information and technology have reached a high level, creating new challenges and problems for universities. Additionally, universities have to change their teaching models and methods to reach contemporary levels. It is possible for universities to revise their missions and visions. These missions should include objectives of education and a suitable strategy that considers the private sector and its expectations from universities. Collaboration with industry and other related sectors can support universities, and encourage them to add courses like "Entrepreneurship" to their curricula. In addition, this encourages universities looking for new partnerships. One such partnership is called KOSGEB (in Turkish), which is a state owned "Small and Medium Enterprises Development Organization". KOSGEB can provide fiscal aid, some refundable and some not, to all small and medium enterprises. KOSGEB also provide huge opportunities to potential entrepreneurs who want to establish a new business through its Entrepreneur Support Program. One component of the program is to provide monetary support – up to 100, 000 TRL in total. In this study, we will discuss the Entrepreneur Support Program of KOSGEB, and whether it is feasible for solving the problem of unemployment after university education. We ask if this program is a good collaboration to help students, and how universities can apply this support program to their academic program.